Low levels of methicillin resistant Staphylococcus aureus in pigs in Malaysia. - Khalid, K. A.; Zakaria, Zunita; Ooi, Peck Toung; McOrist, S. (BMJ Publishing Group, 2009)
The aim of this study was to establish the levels of methicillin resistant Staphylococcus aureus (MRSA) in pigs in Malaysia. Nasal mucosa swabs were obtained from 400 pigs (4-5 weeks old) in 5 farms in Selangor and Perak states [date not given]. Bacteria were cultured from 123 pigs. The numbers of putative mecA + MRSA isolates per farm were 0, 0, 0, 1 and 3, respectively. Farms D and E in Selangor had multiresistant S. aureus, including MRSA compared with the other farms.